Grain refinement promotes the formation of phosphate conversion coating on Mg alloy AZ91D with high corrosion resistance and low electrical contact resistance - Peng Zhou (Elsevier, 2021)
The application of Mg and its alloys in 3C (i.e. Computer, Communication and Consumer Electronic) industries requires a strict combination of corrosion resistance and low electrical contact resistance (ECR). The conventional design of conversion coating relies on a thick and compact layer to offer active protectiveness but compromises the electric conductivity. In this work, phosphate conversion coatings (PCC) with low electrical contact resistance were prepared on the sand-cast and die-cast Mg alloy AZ91D, respectively. The microstructural differences, ECR and corrosion resistance were observed and compared. Results show that the PCCs on die-cast alloy have a thickness of 300-400 nm, and are more compact than those on sand-cast counterparts. Interestingly, PCCs of the die-cast exhibit lower ECR, which indicates a mild impact of the improved compactness on ECR. Meanwhile, corrosion resistance of the PCCs on die-cast alloy is greatly improved, which is attributed to the intensified micro-galvanic effect through the grain refinement of the die-cast alloy. It evidently promotes the electrochemical reactions during the conversion treatment to yield high quality PCC.